Utilizing Social Media as a Collaborative Learning Platform in Early Childhood Education: Opportunities and Challenges - wiwik sulistyawati (Journal of Education Technology and Inovation, 2025)
This study examines the use of social media as a collaborative learning platform in early childhood education. In the digital era, the use of social media is increasingly massive, but its potential in the context of collaborative learning for early childhood still needs to be explored comprehensively. The purpose of the study was to identify opportunities and challenges for implementing social media as a means of collaborative learning in early childhood education institutions. The research methodology uses a qualitative approach with data collection techniques through participatory observation, in-depth interviews with educators and parents, and content analysis on selected social media platforms. The findings were analyzed using the triangulation method to ensure the validity and reliability of the research results. The results of the study can be concluded that social media has transformative potential in the context of PAUD, but its implementation requires a systemic approach that bridges structural gaps and builds the capacity of all stakeholders